SANITASI BAHAN MAKANAN PADA USAHA KATERING DI KOTA YOGYAKARTA = FOODSTUFF SANITATION ON CATERING COMPANIES IN YOGYAKARTA CITY - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
In Yogyakarta City there are so many catering companies with variation of food preparation such as selecting, washing, storing, cooking, and serving of food. It caused variety of food sanitation on serving. Objectives of study are 1. To determine whether vegetables cooked by catering companies in Yogyakarta City are contaminated by the intestinal parasitic agent. 2. To determine the rank of owner's knowledge of selecting, washing, storing, and cooking of the vegetables and also the serving of food. A cross-sectional study on fifteen catering companies in Yogyakarta City were taken into subject randomly. Catering sanitation data were taken by a questionaire, vegetables hygiene data were taken by examination at ParasiÂ¬tology Laboratory, Medical Faculty, Gadjah Mada University. It was around 34,8% of the vegetables were contaminated by intestinal parasites, consist of Hookworm sp. (the higest), Balantidium coli, and Toxoplasma gondii. According to all catering company owners, all of them (100%) washed the vegetables with stream water before cooked, 100% choosed high quality of the vegetables, 57% kept vegetables in refrigerator, 100% feel sure that the vegetables were cooked well and 67% took the vegetables in closed plastic. Conclusions: Vegetables contamination level that cooked by catering companies in Yogyakarta City were high, but with a good knowledge from catering owners in selecting, washing, storing, and cooking, the vegetables can be served free from contamination. Key words: Sanitation - Catering - Vegetables - Parasite - Yogyakarta.